Illustrated key to European genera, subgenera and species groups of Mymaridae (Hymenoptera), with new records for the Czech Republic - Samková, Alena; Janšta, Petr; Huber, John T. (Zootaxa, 2020)
Illustrated keys to females and males of the European genera and subgenera of Mymaridae (Chalcidoidea) are presented, including twenty-four genera plus two subgenera in both of Erythmelus Enock and Polynema Haliday. The key to females also includes three subgenera recognized in Anagrus Haliday, two subgenera in Anaphes Haliday, and two species groups in Anagrus s.s.; males of these either cannot be distinguished or are difficult to key. The species of Mymaridae recorded from the Czech Republic are listed and distribution records are provided based on material in three collections. Seven genera (Anagrus, Caraphractus Walker, Dicopus Enock, Macrocamptoptera Girault, Omyomymar Schauff, Pseudocleruchus Donev & Huber, Stethynium Enock) and 12 species are newly recorded for the country.